2013
DOI: 10.1093/bja/aet064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal magnesium in the presence or absence of local anaesthetic with and without lipophilic opioids: a systematic review and meta-analysis

Abstract: Spinal anaesthesia is the primary anaesthetic technique for many types of surgery. Adjuncts to the local anaesthetics (LA) used in spinal anaesthesia can exhibit undesirable side-effects, limiting their use, but magnesium may have advantages in this respect. We sought randomized control trials (RCTs) in patients undergoing all types of surgery and in women in labour to compare the effect of intrathecal magnesium sulphate ± LA ± lipophilic opioid (experimental group) with the use of either intrathecal lipophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
63
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 51 publications
(39 reference statements)
5
63
1
3
Order By: Relevance
“…When used with local anaesthetic, it resulted in prolongation of analgesia without significant complication (23,24).This prolongation of anaesthesia is consistent with the experimental synergistic action between spinal local aneasthetic and NMDA antagonists like magnesium sulphate, which use anti -nociceptive effects via different mechanisms; (25,26,27) hence the rationale for combining the two. There are no selective NMDA receptor antagonists available for pain management; hence, drugs with other clinical uses, such as magnesium sulphate and ketamine, shown promises as analgesics, have been used.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…When used with local anaesthetic, it resulted in prolongation of analgesia without significant complication (23,24).This prolongation of anaesthesia is consistent with the experimental synergistic action between spinal local aneasthetic and NMDA antagonists like magnesium sulphate, which use anti -nociceptive effects via different mechanisms; (25,26,27) hence the rationale for combining the two. There are no selective NMDA receptor antagonists available for pain management; hence, drugs with other clinical uses, such as magnesium sulphate and ketamine, shown promises as analgesics, have been used.…”
Section: Discussionsupporting
confidence: 58%
“…The magnesium sulfate safety profile has been documented by histopathological analysis in experimental studies (19) .The addition of intrathecal magnesium to intrathecal lipophilic opioid along with local anaesthetics led to delay in the onset of both sensory and motor blockade, along with an increase in the duration of spinal anesthesia. The duration of spinal anesthesia was found to be increased when magnesium was added to opioid with intrathecal local anesthetics compared with a combination of local anaesthetic and opioid mixture(p<0.001) (26) The incidence of adverse events (hypotension, pruritis) was not increased by adding intrathecal magnesium. But it seemed that this drug was enough to provide effective anaesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…11,12 Adding magnesium to intrathecal lipophilic opioid with or without local anaesthesia or local anaesthesia only was associated with a significant increase in the duration of spinal anaesthesia. 13 Animal studies have shown that intrathecal magnesium suppresses nociceptive impulses in a neuropathic pain setting, and potentiates opioid antinociception. 6,14 We are not aware of any All values corrected to first decimal place data are presented as mean ± standard deviation *assessed by Bromage score 9 study comparing two different dosages of magnesium sulphate (50 mg, 100 mg) added as adjuvant to intrathecal 0.5% hyperbaric levobupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium, a non-competitive NMDA receptor antagonist blocks ion channels in a voltage -dependent fashion thereby preventing central sensitization from peripheral nociceptive stimulation leading to enhanced analgesia [25]. However, it has been reported that ketamine and magnesium inhibit the NMDA system differently [23].There are contradictory reports about the role of intravenous magnesium sulphate in reducing intra-and postoperative analgesic requirements [26] and even at high doses, is associated with limited passage across the blood-brain barrier. An inverse relationship has been demonstrated between the severity of pain with different painful medical and surgical conditions and the serum magnesium concentration [25].…”
Section: Discussionmentioning
confidence: 99%